Design and manufacture tri-stimulus colorimete - Ngo, Anh Tuấn; Cao, Xuân Vũ (Journal of Technical Education Science, 2014)
In this study, we designed the model composed of measuring head and the optical system for a colorimeter. The colorimetric is carried out in standard lighting condition D65 of Nichia and color sensor of TAOS. The study focused on processing the measuring data and it is applied to printing quality management.